1987
DOI: 10.1111/j.1432-1033.1987.tb13501.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic antigens of Pseudomonas aeruginosa. The structure of O-specific polysaccharide chains of the lipopolysaccharides from P. aeruginosa II (Sandvik) and V (IM-1, Verder-Evans)

Abstract: The lipopolysaccharides from two serologically related strains of Pseudomonas aeruginosa I1 (Sandvik classification) and V (IM-1, Verder-Evans classification) were isolated by the Westphal method and cleaved with 1 % acetic acid. The 0-specific polysaccharide from Sandvik I1 lipopolysaccharide involved L-rhamnose, N-acetyl-D-quinovosamine, and N-acetyl-D-galactosaminuronic acid in the ratio 2: 1 : 1, as well as 0-acetyl groups. The Verder-Evans V 0-specific polysaccharide was found to contain just the same s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The sites of glycosylation were confirmed by significant downfield displacements of the 13 C NMR signals for the linkage carbons, namely, C-3 of units A and C and C-4 of unit B, as compared with their positions in the non-substituted monosaccharides (Knirel et al, 1986;Lipkind et al, 1988). Analysis of the displacements of the signals for the linkage and neighbouring carbons using known regularities (Knirel et al, 1987;Shashkov et al, 1988) showed that all constituent monosaccharides have the same absolute configuration, namely the D configuration. Therefore, the K19 CPS of strain 28 has the structure shown in Fig.…”
Section: Structure Of the K19 Cps Of A Baumannii 28mentioning
confidence: 84%
“…The sites of glycosylation were confirmed by significant downfield displacements of the 13 C NMR signals for the linkage carbons, namely, C-3 of units A and C and C-4 of unit B, as compared with their positions in the non-substituted monosaccharides (Knirel et al, 1986;Lipkind et al, 1988). Analysis of the displacements of the signals for the linkage and neighbouring carbons using known regularities (Knirel et al, 1987;Shashkov et al, 1988) showed that all constituent monosaccharides have the same absolute configuration, namely the D configuration. Therefore, the K19 CPS of strain 28 has the structure shown in Fig.…”
Section: Structure Of the K19 Cps Of A Baumannii 28mentioning
confidence: 84%
“…Structural analysis of polysaccharides with mass spectrometry, high performance liquid chromatography (10), and NMR (11)(12)(13)(14)(15)(16) has indicated that ␣-D-GalNAcA is one of the most common acidic sugars identified in the O-antigens or capsular polysaccharides of virulent Gram-negative bacteria. Reddy et al (11) suggested that bacterial capsules and LPS containing acidic sugar repeats play an important part in bacteria and host cells interactions.…”
Section: Strains (5-7) Its B-band O-antigen Is a Repeating Linear Tementioning
confidence: 99%
“…the d ‐configuration of GlcNAc II (compare the corresponding glycosylation effects of −2.0 and +0.7 p.p.m. in α1→3‐linked disaccharides of 2‐acetamido‐2‐deoxy‐ l ‐ and d ‐galacturonic acid with d ‐QuiNAc, respectively [23]). This finding confirmed finally 2‐acetamido‐3‐ O ‐[( S )‐1‐carboxyethyl]‐2‐deoxy‐ d ‐glucose ( N ‐acetylisomuramic acid).…”
Section: Resultsmentioning
confidence: 99%